2016
DOI: 10.1016/j.rboe.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar nerve paralysis after forearm bone fracture

Abstract: Paralysis or nerve injury associated with fractures of forearm bones fracture is rare and is more common in exposed fractures with large soft-tissue injuries. Ulnar nerve paralysis is a rare condition associated with closed fractures of the forearm. In most cases, the cause of paralysis is nerve contusion, which evolves with neuropraxia. However, nerve lacerations and entrapment at the fracture site always need to be borne in mind. This becomes more important when neuropraxia appears or worsens after reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The nerve could be damaged by the initial injury as a result of nerve compression from surrounding edema or an injury could result from internal laceration or fibrosis 17. Entrapment of the nerve within fragments of the bone after closed reduction or within scars is another potential cause that can be surgically managed 8. In this reported case, ulnar nerve palsy occurred after a second manipulation of the fracture.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The nerve could be damaged by the initial injury as a result of nerve compression from surrounding edema or an injury could result from internal laceration or fibrosis 17. Entrapment of the nerve within fragments of the bone after closed reduction or within scars is another potential cause that can be surgically managed 8. In this reported case, ulnar nerve palsy occurred after a second manipulation of the fracture.…”
Section: Discussionmentioning
confidence: 89%
“…However, to the best of our knowledge, no literature exists regarding the use of MRI and MRN for the evaluation of ulnar neuropathy after forearm fractures. Nevertheless, MRI was used to help diagnose the status of the ulnar nerve after forearm fractures in two reports 8,20. Ekiz et al recently recommended the use of ultrasonography for such fractures, highlighting its usefulness for detecting nerve injuries 7.…”
Section: Discussionmentioning
confidence: 99%
“…Schwartsmann et al 9 reported a case of a 17-year-old male who suffered a forearm fracture after a skateboard fall. The patient complained of ‘tingling’ of the fifth finger.…”
Section: Resultsmentioning
confidence: 99%
“…Special attention should be paid to whether there is a risk of an open fracture or potential open fracture during physical examination ( 15 ). At the same time, we should focus on the potential forearm nerve injury and evaluate the motor and sensory defects of the anterior interosseous nerve, posterior interosseous nerve, and ulnar nerve ( 16 , 17 ). Meanwhile, an evaluation of blood supply should include the palpation of the radial artery and ulnar artery pulsation and an evaluation of the capillary filling of the fingers, and this should be evaluated several times at different time points.…”
Section: Discussionmentioning
confidence: 99%